Caracterização molecular do Htlv-1 em pacientes com paraparesia espástica tropical/mielopatia associada ao HTLV-1 em Belém, Pará - SOUZA, Lucinda Assunção Gustavo (2013)
The present study evaluated the occurrence of HTLV-1 and its subtypes in blood samples of patients presenting symptoms of tropical spastic paraparesis/HTLV-1 associated myelopathy. The detection of HTLV infection was performed by serological and molecular assays. Five patients were infected by HTLV-1 of the Cosmopolitan subtype, subgroup Transcontinental. The results confirm the occurrence of HTLV-1 infection among patients with clinical diagnosis of tropical spastic paraparesis/HTLV-1 associated myelopathy in Belém, Pará.